Feasibility of Using Radio Frequency Identification to Facilitate Individual Producer Responsibility for Waste Electrical and Electronic Equipment. (28th February 2013) - O'Connell, Maurice; Hickey, Stewart; Besiou, Maria; Fitzpatrick, Colin; Van, Luk N.
Summary Regulatory measures that hold producers accountable for their products at end of life are increasingly common. Some of these measures aim at generating incentives for producers to design products that will be easier and cheaper to recover at the postconsumer stage. However, the allocation of recovery costs to individual producers, which can facilitate realization of the goals of these policies, is hindered by the practical barrier of identification and/or sorting of the products in the waste stream. Technologies such as radio frequency identification (RFID) can be used for brand or model recognition in order to overcome this obstacle. This article assesses the read rate of RFID technology (i.e., the number of successful retrievals of RFID tag data ["reads"] in a given sample of tagged products) and the potential role of RFID tags in the management of waste electrical and electronic equipment (WEEE) at current levels of technical development. We present the results of RFID trials conducted at a civic amenity site in the city of Limerick, Ireland. The experiment was performed for fixed distances up to 2 meters on different material substrates. In the case of white goods (i.e., large household appliances), a 100% read rate was achieved using an RFID handheld reader. High read rates were also achieved for mixed WEEE. For a handheld scan of a steel cage containing mixed WEEE, read rates varied from 50% to 73% depending on the ultrahigh frequency (UHF) metal mount tag employed and the relative positioning of the tags within the cage. These results confirm that from a technical standpoint, RFID can achieve much greater brand or model identification than has been considered feasible up to now, and thus has a role to play in creating a system that allocates recovery costs to individual producers.